2011
DOI: 10.1002/meet.2011.14504801189
|View full text |Cite
|
Sign up to set email alerts
|

Personal information management practices of teachers

Abstract: Teaching is an information-rich profession with increasing demands on accountability and performance. Ideally, a well-managed information space provides teachers with relevant information when they need it, thus increasing their efficiency and efficacy and conceivably improving teaching quality. Little is known about teacher personal information management (PIM). This exploratory study employed interviews to establish a context to study teacher PIM. The study found that teachers draw information from a variety… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
12
0
3

Year Published

2012
2012
2023
2023

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 22 publications
(20 citation statements)
references
References 28 publications
(30 reference statements)
0
12
0
3
Order By: Relevance
“…This paper provides an exploratory foundation for future work on teacher information seeking behavior and personal information management. Like our previous study (Diekema and Olsen, 2011), this study also builds on prior work on information behavior, namely that of Kwasňik (1989, 1991), Barreau (2008; 1995), and Jones (2007). In addition, this study incorporates research on relevance by Saracevic (1975, 2007a, 2007b) and others.…”
Section: Introductionmentioning
confidence: 76%
See 1 more Smart Citation
“…This paper provides an exploratory foundation for future work on teacher information seeking behavior and personal information management. Like our previous study (Diekema and Olsen, 2011), this study also builds on prior work on information behavior, namely that of Kwasňik (1989, 1991), Barreau (2008; 1995), and Jones (2007). In addition, this study incorporates research on relevance by Saracevic (1975, 2007a, 2007b) and others.…”
Section: Introductionmentioning
confidence: 76%
“…As such, PIM revolves around the three intricately related activities of finding and re‐finding, keeping (storing), and organizing and interpreting information (Barreau, 1995; Boardman, 2004; Jones, 2007; Lansdale, 1988). Teachers have not been the specific focus of PIM studies except for our study of 5 secondary (middle) school teachers (Diekema & Olsen, 2011). This study found that teachers' personal information spaces were similar in their physical structure and content but differed in the way information was organized within it.…”
Section: Introductionmentioning
confidence: 99%
“…Initially, responses to the interview questions were analyzed for PIM‐ and information‐related features using thematic analysis (Boyatzis, ). This analysis was carried out on a subset of the data for PIM features and all the data for information features and provided input for two conference papers (Diekema & Olsen, , ). Informed by these themes and a literature review on teacher information behavior, an initial codebook was created for the in‐depth analysis of all the data.…”
Section: Methodsmentioning
confidence: 99%
“…This study built on prior work on information behavior and personal information management, namely, that of Kwasnik (1989Kwasnik ( , 1991, Barreau (2008Barreau ( , 1995, and Jones (2007). It also expanded on an earlier study of five middle school teachers, Grades 6 to 8 (Diekema & Olsen, 2011). The present study included eight elementary school and nine high school teachers and two additional middle school teachers (seven middle school teachers total).…”
mentioning
confidence: 99%
“…Student teachers who lack confidence often restrict themselves to readily available and accessible sources (Williams & Coles, ). Diekema and Olsen () interviewed teachers and observed several ways to find relevant information, including the maintenance of collections of resources, reliance on colleagues' advice, and online resources available on the web. Scaffolding student teachers to develop effective information‐seeking behaviours should be of concern for teacher education and professional development, but very little is known with regards to the underlying SRL processes that mediate learning and task performance.…”
Section: Introductionmentioning
confidence: 99%